Marketing channels, their effectiveness and perceived constraints in milk processing in NCR - GILL, RESHMA; SHARMA, J P; BURMAN, R R; SHARMA, R R; KAR, AMIT (The Indian Journal of Animal Sciences, 2016)
Major concern of today’s agriculture and allied sector is to tumble wastage and increase farmers’ income. Post harvest operation and value addition of the farm products is one important way to attain this goal. Even if Indian dairy sector has a well renowned position in the world milk market in terms of production, processing and value addition percentage at the farmer level is not in a recognisable stage. Marketing channels, marketing efficiency and price spread of the identified marketing channels among milk producers and milk processors have been analysed here. Comparative study of the producers share in consumer’s rupee of value added milk products and liquid milk showed a significant difference. It was more than 96% in processing of milk and nearly 85% in raw milk. Marketing efficiency analysis showed that channel I (Producer –Consumer) was the most efficient in both group. Price of value added food (Mean Ranks of Friedman’s test is 9.10) was the most important factor which attracts the milk processors to take value addition and post harvest management decisions. Infrastructure related constraints (Mean Rank of Kruskal-Wallis test 28.70) were the major constraint faced by the dairy processors. Under that lack of power and electricity and non-availability of machineries in local places (Mean Ranks of Friedman’s test is 7.70) were identified as the major constraints in the study area. As per the milk producers, technical inhibiting factors (Mean Rank of Kruskal-Wallis test 40.25) prevent them from undertaking the post harvest operations and value addition in raw milk.